2021
DOI: 10.5312/wjo.v12.i2.69
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of joint awareness after acetabular fracture: Validation of the Forgotten Joint Score according to the COSMIN checklist protocol

Abstract: BACKGROUND A fracture of the acetabulum is an uncommon, but serious injury. Established outcome tools do not reflect the patient’s perspective after fracture of the hip joint. Originally designed for post-arthroplasty patients, the Forgotten Joint Score (FJS) is a patient-reported outcome measurement (PROM) tool evaluating the disease-specific health-related quality of life (HR-QoL). AIM To validate the FJS in patients after acetabular fracture. METHODS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…The effect of BMI on results from different PRO questionnaires are somehow conflicting [51][52][53]. FJS-12 has been proven to be simple, valid and reliable in original and translated versions [3,17,20,[54][55][56]. A study in New York found that although patients who were obese (BMI ≥ 30 kg/m 2 ) and received primary TKA provided lower post-surgery FJS-12 scores, statistical significance was not found [57].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The effect of BMI on results from different PRO questionnaires are somehow conflicting [51][52][53]. FJS-12 has been proven to be simple, valid and reliable in original and translated versions [3,17,20,[54][55][56]. A study in New York found that although patients who were obese (BMI ≥ 30 kg/m 2 ) and received primary TKA provided lower post-surgery FJS-12 scores, statistical significance was not found [57].…”
Section: Discussionmentioning
confidence: 99%
“…FJS-12 is based upon the assumption that the goal of total knee arthroplasty is a joint patient can “forget” about. Studies started using FJS-12 as the sole PRO assessment tool [ 19 , 20 ] to access knee functions and used to assess the long-term results after TKA [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, surgeons must undergo a specific training for years for specialization in pelvic surgery. Technical advancements in imaging and surgical instruments may lower the learning curve and lead to better surgical results [7][8][9][10][11][12] . Historically, treatment of pelvic fractures was open reduction and plate osteosynthesis of the pelvic ring.…”
Section: Introductionmentioning
confidence: 99%